INDEPENDENT STUDY. - Littleton, A. C. (The Accounting Review, 1933)
Abstract The article presents information that bright students at the University of Illinois, in the United States, are encouraged to do a portion of their study without class room attendance. This may be done at the student's option either by preparing a written thesis or by doing special reading. The senior thesis option has been available for about ten years. It is required of seniors who expect to be graduated with High Honors but is open to others by special permission. The intention is that the student will make an intensive examination into some topic of personal interest; perhaps it will be in regard to some subject matter which was but briefly treated in one of his classes, frequently the study is more directly related to his own specific business intentions or to some family enterprise. The administration of the work is simple for after the student has selected his topic he works individually with the faculty man who is thought to be best acquainted with the field of his study. The few conferences which are necessary regarding sources, outline and occasional "snags" are no great burden on the teacher and reading the finished work is more interesting than otherwise.